2007
DOI: 10.1111/j.1365-2788.2006.00947.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of facial expressions of emotion by children with intellectual disabilities of differing aetiology

Abstract: Findings support previous evidence of emotion recognition abilities commensurate with overall developmental level in children with FXS or NSID, but not DS. They also suggest, however, that syndrome-specific difficulties may be subtle and detectable, at least in smaller-scale studies, only in comparison with TD matches, and not always across syndromes. Implications for behavioural phenotype theory, educational interventions and future research are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
85
4
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(106 citation statements)
references
References 64 publications
13
85
4
4
Order By: Relevance
“…As in WS but to a lesser extent, skills for identity recognition are better than those for recognizing facial expressions in DS (Williams, Wishart, Pitcarin, & Willis, 2005;Wishart & Pitcarin, 2000). Across labeling, matching and identification tasks with static stimuli, individuals with DS consistently perform significantly lower than TD peers of the same MA (Kasari, Freeman, & Hughes, 2001;Hippolyte et al, 2009;Hippolyte, Barisnikov, Van der Linden, 2008;Porter et al, 2007;Williams et al, 2005;Wishart et al, 2007;Wishart & Pitcairn, 2000). However, these results seem to be observed only from a mental age of 4 years and above (Kasari et al, 2001).…”
Section: Recognition Of Emotional Facial Expressions In Down Syndromecontrasting
confidence: 37%
See 2 more Smart Citations
“…As in WS but to a lesser extent, skills for identity recognition are better than those for recognizing facial expressions in DS (Williams, Wishart, Pitcarin, & Willis, 2005;Wishart & Pitcarin, 2000). Across labeling, matching and identification tasks with static stimuli, individuals with DS consistently perform significantly lower than TD peers of the same MA (Kasari, Freeman, & Hughes, 2001;Hippolyte et al, 2009;Hippolyte, Barisnikov, Van der Linden, 2008;Porter et al, 2007;Williams et al, 2005;Wishart et al, 2007;Wishart & Pitcairn, 2000). However, these results seem to be observed only from a mental age of 4 years and above (Kasari et al, 2001).…”
Section: Recognition Of Emotional Facial Expressions In Down Syndromecontrasting
confidence: 37%
“…No significant differences have been found between individuals with DS and those with nonspecific intellectual disabilities or individuals with Fragile-X syndrome (Williams et al, 2005;Wishart et al, 2007;Wishart & Pitcairn, 2000). Yet, despite the lack of significant differences between groups, in the same studies, only participants with DS performed significantly lower than TD children matched on MA (Williams et al, 2005;Wishart et al, 2007;Wishart & Pitcairn, 2000).…”
Section: Recognition Of Emotional Facial Expressions In Down Syndromementioning
confidence: 66%
See 1 more Smart Citation
“…Again, the results indicated that children with DS were less accurate and slower in response to MA-matched controls. Furthermore, unlike the TD group, the accuracy of the children in DS group was not sensitive to orientation of the faces (see also, Williams et al, 2005;Wishart, Cebula, Willis & Pitcairn, 2007, for similar studies).…”
Section: Down Syndromementioning
confidence: 89%
“…Relatively little research has been carried out on face recognition in Down syndrome (DS) (see Williams et al, 2005;Wishart, et al, 2000Wishart, et al, , 2007for exceptions). On the basis of existing data, it has been claimed that individuals with DS exhibit a 'global' style in visuospatial processing (e.g., Bellugi et al, 1999), which one may take to be synonymous with visual processing that is more holistic and less featural.…”
Section: Discussionmentioning
confidence: 99%